Effects of dietary yeast hydrolysate on the growth, antioxidant response, immune response and disease resistance of largemouth bass (Micropterus salmoides). Issue 94 (November 2019) - Gong, Yulong; Yang, Fan; Hu, Junpeng; Liu, Cui; Liu, Haokun; Han, Dong; Jin, Junyan; Yang, Yunxia; Zhu, Xiaoming; Yi, Jianhua; Xie, Shouqi
Abstract: A 56-day growth trial was conducted to investigate the effects of dietary yeast hydrolysate on the growth performance, antioxidation, immune response and resistance against Aeromonas hydrophila in largemouth bass. Four experimental diets were prepared with yeast hydrolysate levels of 0% (Y0), 1.5% (Y1.5), 3.0% (Y3.0) and 4.5% (Y4.5). Each diet was randomly assigned to triplicate 150-L tanks and each tank was stocked with 30 largemouth bass (initial body weight, IBW = 7.71 ± 0.02 g). A challenge test was carried out after the feeding trial by injecting A. hydrophila intraperitoneally for 4-day observation. The results showed that the FBW and WGR in Y1.5 group were significantly higher than those in Y0 group ( P < 0.05 ) and the feed conversion ratio (FCR) got the lowest value in Y1.5 group. And the hydrolysate supplement significantly increased the 4-day cumulative survival rate after the bacterial challenge ( P < 0.05 ). The plasma malondialdehyde was lower in the yeast hydrolysate supplement groups in both pre- and post-challenge test ( P < 0.05 ), while the plasma C3 increased ( P < 0.05 ). In post-challenge test, the plasma superoxide dismutase (SOD) and catalase (CAT) activities increased in the Y1.5 and Y3.0 groups respectively ( P < 0.05 ), and plasma lysozyme in Y1.5 group and the plasma IgM in Y3.0 group were higher than those in others respectively ( P < 0.05 ). For the q-PCR results, in post-challenge test, the hepatic hep2 expression level in Y1.5 and Y4.5 groups were both significantly higher than those in others ( P < 0.05 ), as well as il-8 in Y3.0 group. The spleen hif-1alpha and tgf-beta1 expression levels in Y4.5 group were all significantly lower than those in others ( P < 0.05 ), while the gilt was significantly higher ( P < 0.05 ) in the post-challenge test. And the expression levels of spleen tnf-alpah1 in Y1.5 and Y3.0 groups and il-8 in Y3.0 group were all significantly higher than those in other groups ( P < 0.05 ) in the post-challenge test. The head kidney gilt expression level was significantly higher in the yeast hydrolysate supplement groups compared with the Y0 group ( P < 0.05 ), and the head kidney il-8 expression level in Y1.5 group was significant higher than those in other groups in post-challenge test ( P < 0.05 ). The present results indicated dietary yeast hydrolysate improved the antioxidant ability and enhanced the immune response of largemouth bass without negative effect on growth. And 1.5% or 3.0% of dietary yeast hydrolysate was recommended for largemouth bass based on the present results. Highlights: 1.5% or 3.0% dietary yeast hydrolysate improved the antioxidation and immunity of largemouth bass without negative effect. The dietary yeast hydrolysate enhanced the liver antibacterial activity by stimulating the hep2 expressions. The dietary yeast hydrolysate improved antioxidation through the gilt and hif-1alpha expressions. The dietary yeast hydrolysate decreased the inflammation of head kidney by regulating proinflammatory cytokines.